Characteristic of Pterygium Among Merchants in Tanah Lot Coastal Tourism Area, Bali - Putri, Esha Manahcika; Permatananda, Pande Ayu Naya Kasih; Putra, I Putu Rustama (Smart Medical Journal, 2025)
Introduction: The high incidence of pterygium in Indonesia, especially in Bali, can decrease the quality of life due to impaired vision or blindness related to visual axis disruption. Pterygium is characterized by fibrovascular tissue growth extending from the nasal area or temporal limbus towards the cornea. Exposure to UV rays and activities in dusty or sandy areas are contributing factors to the increased incidence of pterygium. The Tanah Lot Tourist Attraction Area is a coastal tourism site where the majority of the local community engages in trading activities. This research aims to investigate the characteristics of Pterygium among traders in the Tanah Lot Tourist Attraction AreaMethods: It was an observational-descriptive study with a cross-sectional design. The sample consisted of 100 respondents selected through consecutive sampling based on inclusion criteria. Data were obtained through questionnaire-based interviews and documented using a digital camera. The collected data will be descriptively analyzed using SPSS version 25.0, employing univariate analysis and cross-tabulation to observe the characteristics of pterygium based on age, gender, exposure history, and duration of exposure.Results: The research findings reveal that the majority of pterygium patients are aged between 46 and 55, female, have a history of sun exposure for more than 10 years, and spend more than 4 hours outdoors. Most subjects in the study have grade 2 pterygium, which indicates growth beyond the corneal limbus but not exceeding 2 mm onto the cornea.Conclusion: This study provides further insight into the characteristics of pterygium patients, aiming to raise awareness about the continuous hazards of UV exposure.